KAJIAN KELESTARIAN IKAN LOKAL (IKAN TAPAH DAN KELEMAK) DI WILAYAH KABUPATEN KAMPAR PROVINSI RIAU - Pareng Rengi; Bustari '; Sumarto ' (Fakultas Perikanan dan Kelautan, Universitas Riau, 2013)
Productivity of Tapah fish (Wallago leeri) and kelemak fish (Leptobarbushoeveni Blkr) in Kampar district has been decreased every year. It’s indicates thatthis species in extinct conditions and should be a priority to recovery. Someactivity which can do to recovery this species with know how much stock thisspecies in Kampar district. Recovery this species can do with cage aquaculturemethod and areas of fisheries conservation.Keywords: Wallago leeri, Leptobarbus hoeveni Blkr, fresh water, stock